Clinical and Bacteriological Profile of UTI Patients in Medicine Department in a Teaching Hospital of Bangladesh - Ahmmed, Ferdaus; Hossain, Md Enayet; Hossain, Md Guljar; Karmaker, Gobinda; Kabir, Mohammed Ruhul; Chowdhury, Iqbal Ahmed; Paul, Mukul Chandra; Pal, Hitangshu Shekhar (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Introduction: Urinary tract infections (UTIs) encompass a wide array of infections, accounting for a vast number of community as well as hospital acquired infections. This study was undertaken to evaluate the clinical presentations and bacteriological profile of UTI patients in indoor setting. Methods: This 6 months cross-sectional study enrolled 100 patients admitted in Medicine department of Sylhet MAG Osmani Medical College Hospital with symptoms and signs of UTI subsequently confirmed by compatible investigations including urine culture. Results: Among 100 patients of UTI, maximum were females (67%) and the male female ratio was 0.49: 1. The most common age group was 46–60 years (34%). Majority (68%) of the patients had upper UTI while lower UTI constitutes 32%.66% of the patients had complicated while 34% have uncomplicated UTI.18% of the patients had recurrent UTI. Most of the patients had fever (55%), followed by loin pain (37%) as their presenting symptoms. The most common risk factor was loss of host defense 38% (diabetes mellitus/ use of immunosuppressive drugs).Out of 100, 60 urine samples were positive for pathogenic organisms. Escherichia coli was isolated in 41 (68.3%) of the positive samples, followed by Klebsiella sp 13 (21.6%), Pseudomonas sp 3 (5%) Proteus sp 2 (3.3%) Staph. Aureus 1(1.66%). Conclusion: The most common clinical presentations of UTI in admitted UTI patients are fever and loin pain. Diabetes mellitus is the most important risk factor. Mainly Gram negative bacilli were found to be responsible for UTI and most frequent isolated bacteria was E-coli. J Bangladesh Coll Phys Surg 2021; 39(2): 106-113